2000
DOI: 10.1046/j.1365-2990.2000.026002150.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor neuronal death in sporadic amyotrophic lateral sclerosis (ALS) is not apoptotic. A comparative study of ALS and chronic aluminium chloride neurotoxicity in New Zealand white rabbits

Abstract: Whether diseased motor neurones in sporadic amyotrophic lateral sclerosis (ALS) die via apoptosis is unknown. Because this relates primarily to difficulties in utilizing post-mortem tissue from end-stage disease, motor neurone degeneration in ALS spinal cord was compared with that of a model of a chronic motor neurone degeneration. Degenerating motor neurones in ALS, identified by ubiquitin immunoreactivity, did not demonstrate the morphological characteristics of apoptosis and were not c-Jun immunoreactive or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 19 publications
5
28
0
2
Order By: Relevance
“…The author of that study has also documented DNA fragmentation in anteriorhorn gray matter of the spinal cord and motor cortex of ALS cases by gel electrophoresis (38), a technique not frequently used in the nervous system to identify apoptosis since, in many neurological situations, it is difficult to obtain samples with a sufficiently high proportion of dying cells. In contrast to all these positive findings, other groups, using similar techniques and tissue samples, have failed to provide any evidence of internucleosomal cleavage of DNA in postmortem tissue from human ALS cases or from animal models of the disease (32,41,42). Although the actual reason for these divergent results is unclear, they cast doubt on the reliability and even the specificity of such findings.…”
Section: Expression Of Apoptotic Markersmentioning
confidence: 94%
“…The author of that study has also documented DNA fragmentation in anteriorhorn gray matter of the spinal cord and motor cortex of ALS cases by gel electrophoresis (38), a technique not frequently used in the nervous system to identify apoptosis since, in many neurological situations, it is difficult to obtain samples with a sufficiently high proportion of dying cells. In contrast to all these positive findings, other groups, using similar techniques and tissue samples, have failed to provide any evidence of internucleosomal cleavage of DNA in postmortem tissue from human ALS cases or from animal models of the disease (32,41,42). Although the actual reason for these divergent results is unclear, they cast doubt on the reliability and even the specificity of such findings.…”
Section: Expression Of Apoptotic Markersmentioning
confidence: 94%
“…Real-time PCR of transgene copy numbers revealed that transgenic pigs carried various numbers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) of the transgene (Supplementary information, Table S1). Using immunohistochemistry staining with an antibody specific to hSOD1, we could confirm the expression of transgenic hSOD1 in the lumbar spinal cords of a stillborn transgenic pig, but not in a wild-type one ( Figure Figure 1 Generation of hSOD1 (G93A) transgenic pigs.…”
Section: Generation Of Human Sod1 (Hsod1) (G93a) Transgenic Pigsmentioning
confidence: 99%
“…These transgenic SOD1 mouse models carry a greatly elevated protein load compared with human ALS tissues, and these animals exhibit some phenotypic features, such as intracytoplasmic vacuoles derived from the mitochondria and the endoplasmic reticulum, which are rarely found in human ALS tissues [11][12][13]. In terms of the mechanisms of neuronal death in ALS, most evidence from mouse models suggests that apoptosis may play a crucial role in the death of motor neurons [14][15][16]; however, conclusive evidence of apoptosis has been difficult to detect in humans [17][18][19][20]. In addition, intranuclear inclusions were seen in the brains of ALS patient with SOD1 mutations [21][22][23], which have nevertheless not been found in transgenic mutant SOD1 mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…These include cell shrinkage, chromatic condensation, DNA fragmentation, and increased expression of both proapototic (c-Jun, c-Fax, Bax, p53, APO-1/Fas-CD95, Fas, Fas-L, caspase 8 and 9, activated caspase 3, tumor necrosis factor R1/p55), and antiapoptotic proteins (Bcl-2, Bcl-x), or DNA repair enzymes, such as Ref-1 and the co-expressed GADD45 [13, 16,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. However, other groups have observed little or no evidence of apoptotic neuronal cell death associated with neurodegenerative diseases [24,[37][38][39][40][41][42][43]. These studies have relied on the presence of Table 2).…”
Section: Findings On Apoptosis In Human Post Mortem Brainmentioning
confidence: 99%